A Critical Review on “Charakokta Deepaniya Mahakashaya” - Rankawat, Shweta; Singh, Manpreet; Sharma, Ashwini Kumar; Soni, Pradeep (International Research Journal of Ayurveda & Yoga, 2023)
The fourth chapter of Charaka samhita is related to fifty various groups. In each group, 10 herbs are included having common action. Deepaniya mahakashaya is pronounced for action related to digestive fire. Charaka Samhita’s Deepniya Mahakashaya is a significant mahakashaya. Deepana translates as Agni stimulation (i.e Digestive fire). Due to people’s inability to adhere to diet regulations due to sedentary lifestyles, the importance of this Mahakashaya has grown in day-to-day practise. which ultimately causes Agni’s vitiation. Agni plays a vital role in maintaining health and balancing the equilibrium of Dosha, Dhatu and Mala. So, to bring the function of Agni to normalcy, besides maintaining proper diet and regimen, Deepaniya drugs are advised. The purpose of this article is to further explain the concepts of Deepana, Raspanchaka (Rasa, Guna Virya, Vipaka and karma) of that particular drugs that are discussed in Charakokta Deepaniya Mahakshaya.